2006
DOI: 10.1039/b608425g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent “light-up” bioprobes based on tetraphenylethylene derivatives with aggregation-induced emission characteristics

Abstract: Aggregation in poor solvents and complexation with calf thymus DNA and bovine serum albumin turn "on" the fluorescence of tetraphenylethylene derivatives, due to the restriction of intra-molecular rotations of the dyes in the aggregates and complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
269
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 518 publications
(274 citation statements)
references
References 46 publications
1
269
0
4
Order By: Relevance
“…43,44 TPE is a bulky and sterically hindered group with great potential as a building block for development of novel PIMs for membrane-based separations. In this study, we report for the first time the design and synthesis of tetraphenylethylene-based PIMs, as illustrated in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 TPE is a bulky and sterically hindered group with great potential as a building block for development of novel PIMs for membrane-based separations. In this study, we report for the first time the design and synthesis of tetraphenylethylene-based PIMs, as illustrated in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…TPE 1 and its diphenylated derivative 2 were readily prepared by simple McMurry reactions ͑Scheme 1͒. 22 Almost no photoluminescence ͑PL͒ signals can be detected from their dilute solutions in acetonitrile and tetrahydrofuran ͑THF͒, revealing that the dyes are practically nonluminescent when molecularly dissolved in their good solvents. As shown in Fig.…”
mentioning
confidence: 99%
“…Thanks to the steric effect of the peripheral phenyl rings, the dye molecules take propellerlike, nonplanar conformations ͑see crystal structure of 1 shown in Scheme 1͒, which prevents them from packing via -stacking interactions and quenching by such detrimental species as excimers. 22 The restriction of intramolecular rotations in the aggregates blocks the channel of nonradiative decay, hence changing the nonluminescent dyes to strong emitters.…”
mentioning
confidence: 99%
“…A sensor array based on analyte-specific patterns arising from the differential binding affinity of a set of nonspecific receptors is attractive, because this sensing approach simplifies the sensor design. [15,16] Recently, we [17] and others [18] have demonstrated that aggregation-induced emission (AIE)-active materials, first reported by Tang and co-workers, [19] have potential utility in the sensing fields. [20] AIE-active molecules show no emission in solution but an intense emission when aggregated or in the solid state because of the restriction of intramolecular rotations that prevent nonradiative deactivation for fluorescence quenching.…”
Section: Introductionmentioning
confidence: 96%